P91 Mechanisms of action in group-based interventions (magi) study: a framework of change processes in group-based health interventions. (2nd September 2017) - Borek, AJ; Smith, JR; Abraham, C; Greaves, CJ; Morgan-Trimmer, S; Gillison, F; Jones, M; Tarrant, M; McCabe, R
Abstract : Background: Groups are often used to promote personal and health-related psychological and behavioural change. Although there is considerable literature on group dynamics and intra- and inter-personal change processes in groups, this knowledge is dispersed across different disciplines and rarely used in the design, delivery and evaluation of group-based health interventions. The aim of the Mechanisms of Action in Group-based Interventions (MAGI) study was to identify and enhance understanding of change processes in group-based health interventions by (1) developing a conceptual framework of change processes in groups, (2) identifying examples of these processes and practical strategies for facilitating them, and (3) exploring potential relationships between group processes and intervention engagement and outcomes in three group-based weight loss interventions. Methods: Qualitative methods were used to develop the conceptual framework and identify examples of change processes and practical strategies. This involved (1) reviewing literature on theories of group dynamics and change in groups, qualitative studies, taxonomies of behaviour change techniques, and assessment tools to measure group processes; (2) reviewing and coding content of intervention manuals and 38 transcripts of group session recordings from three studies of group-based weight loss interventions; and (3) consultations with researchers, practitioners, facilitators and participants involved with group-based interventions. Further 24 transcripts of group sessions from one of the weight loss studies were coded using the framework and analysed to explore associations with intervention engagement and outcomes. Results: Key concepts and processes were synthesised into a framework of change processes in group-based health interventions. Processes were categorised into: (1) group dynamic and development processes, (2) inter-personal change processes, and (3) intra-personal change processes in groups. Examples of practical strategies to facilitate and manage these processes were identified and categorised into: (1) group design elements, (2) group set-up tasks, (3) group facilitation strategies, and (4) group closure tasks. Work to identify examples of how group interaction and group processes might link with participant engagement and outcomes is still in progress but will be presented. Discussion: The presented framework integrates a large body of literature on change processes in groups, and provides examples of practical strategies that can be used to instigate and facilitate change processes in group-based health interventions. It provides a practical tool for researchers and practitioners that can be used to design and deliver better group-based health interventions, train group facilitators, and guide evaluations of group-based interventions, with a view to optimising intervention engagement and outcomes.